New management systems as an instrument of implementation sustainable development concept at organizational level - Ejdys, Joanna; Matuszak-Flejszman, Alina (Technological and Economic Development of Economy, 2010)
Diversity of contemporary management concepts, short life duration of some of them, fashion of implementing popular solutions, indiscriminate adoption of management systems in companies simultaneously with a long period of waiting for positive effects of implemented changes and decreasing involvement of employees lead to the situation in which many companies still face unresolved dilemma of choosing the right strategy of acting that ensures sustainable development of a unit. Therefore, new solutions should be treated as one of the elements of organization improvement, not as an objective as such, and as the way of solving the existing problems. One of the ways of realizing sustainable development principles at the level of an organizational unit is implementation of normalized systems elaborated by International Organization for Standardization (ISO). The article presents a proposal of the way of implementing sustainable development concept at organizational level using three systems: quality, environmental, occupational health and safety management.Article in English.Naujos valdymo sistemos kaip instrumentai įgyvendinant darnios plėtros koncepciją organizaciniu lygmeniuSantrauka. Šiuolaikinių valdymo koncepcijų įvairovė ir jų trumpalaikiškumas (kai kurių), polinkis įgyvendinti populiarius sprendimus, beatodairiškas valdymo sistemų diegimas ilgai laukiant teigiamų pokyčių, taip pat darbuotoju dalyvavimo, priimant sprendimus, mažinimas sukuria situaciją, kai daugelis bendrovių vis dar susiduria su neišspręsta dilema - pasirinkti tinkama strategiją darniam organizacijos vystymuisi užtikrinti. Todėl nauji sprendimai turėtų būti traktuojami kaip organizacijos tobulinimo elementai, o ne kaip panacėja esamoms problemoms išspręsti. Vienas darnaus vystymosi principų įgyvendinimo būdų ‐ diegti standartizuotas sistemas, parengtas Tarptautines standartizacijos organizacijos (ISO) įmonėse. Straipsnyje siūloma darnaus vystymosi koncepcija organizacijos lygmeniu įgyvendinti naudojant tris valdymo sistemas: kokybės, aplinkos apsaugos, darbuotojų saugos ir sveikatos valdymo.Reikšminiai žodžiai: darnus vystymasis, aplinkos valdymas, kokybės valdymas, saugos valdymas.First published online: 09 Jun 2011